Refugee women in the media – prevalence, representation and framing in international media coverage. - Rothenberger, Liane; Schmitt, Melanie (Journal of Ethnic & Migration Studies, 2024)
Are refugee women invisible in the media? Extant media portrayals often make use of stereotypical representations, in that women are represented as vulnerable and passive victims. Within the theoretical frameworks of agenda setting and framing, vulnerability and agency, digital emotion contagion and distant suffering, this study investigates media coverage on refugee women by four popular international news outlets on the basis of their YouTube presence from 2011 to 2021. We applied automated data gathering to extract relevant videos which were manually coded and analyzed. In addition, we applied an automated topic modeling and sentiment analysis. The results are ambiguous but in general reflect existing findings: refugee women are marginalized in media coverage, and their portrayal is often stereotypical presenting them as vulnerable victims. The results highlight the need to sensitize journalists for a non-stereotypical reporting and the broader public for a more critical stance towards media coverage of refugee women.